A STUDY ON RELATION BETWEEN PCOS AND HEATH RELATED PHYSICAL FITNESS - Jairaj. J; Dr. Aji. P.L (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The purpose of the study was to analyse the relation between PCOS and health related physical fitness. 346 female students in the age group 18 -.21yrs (Under graduate students) from different colleges across the state were randomly selected and administered with a clinical tool to assess PCOS. The clinical tool to identify PCOD developed to Sue. D Pederson. M.D et.al. was used. After administering the clinical tool they were tested for health related physical fitness using the same battery as used in the TPFP program where 16,28,943 students in 2007 and 23,34,739 students in 2009 were tested. The scores of the TPFP variables were used as fitness scores, that of clinical tool to categorize PCOD and non PCOD groups were chosen and used as seven independent variables and treated with MANOVA, Descriptive analysis, univariate analysis and pair wise comparison statistical analysis and interpretations were made using MANOVA and analysis of variance. The results of the study shows that irrespective of development PCOS is prevalent among females of reproductive age in large numbers and as studies put forward the importance of early detection and management awareness campaigns may be began as a community health program.